Correction to: Long-term survival after hepatectomy for metachronous liver metastasis of pancreatic ductal adenocarcinoma: a case report - Chikanori Tsutsumi; Toshiya Abe; Tomohiko Shinkawa; Kazuyoshi Nishihara; Sadafumi Tamiya; Toru Nakano (Surgical Case Reports)
An amendment to this paper has been published and can be accessed via the original article.